THE CONTROL OF A TOY TRAIN SYSTEM USING THE PID CONTROLLER IN MATLAB / SIMULINK - Gheorghe GÎLCĂ; Ilie BORCOȘI (Fiabilitate şi Durabilitate)
Model-based systems engineering is widely used in the automotive and avionics domain but less in the railway domain. This paper shows how Matlab / simulink can simulate a toy train system and then control it with the PID control algorithm. To this end, an executable model has been implemented which allows for train movement simulation, this means that the engine first went forward, then backward.